Possibilities of the Reclamation of Wastewater in Small Abattoirs Combined with Rainwater Harvesting - Hancz, Gabriella (International Journal of Engineering and Management Sciences, 2023)
The purpose of the study is to review the extent to which waste water from small mobile slaughterhouses can be reclaimed along with the basic cases and the purpose for which this can be realized. Keeping the criteria of sustainability in mind, I identify the possible and at the same time reasonable combinations of technology, highlighting and presenting in more detail those that include the utilization of waste water and the utilization of rainwater. I will describe the limiting factors - site features, environmental protection and health regulations - which are decisive in which alternative can be chosen during a specific installation.